2017
DOI: 10.1111/sode.12233
|View full text |Cite
|
Sign up to set email alerts
|

Observed and parent‐reported conscience in childhood: Relations with bullying involvement in early primary school

Abstract: This exploratory study aimed to examine which components of early childhood conscience predicted bullying involvement around school entry. In the population-based Generation R Study, teacher reports of bullying involvement and parent reports of conscience were available for 3,244 children (M age 5 6.7 years). Higher levels of overall conscience predicted lower bullying perpetration scores, independently of intelligence quotient, temperamental traits and sociodemographic characteristics. Particularly, the subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Repo and Sajaniemi (2015) examined teachers' institutional and pedagogical practices of prevention of preschool bullying, whereas Yörük (2016) investigated the nature and the extent of preschool bullying from the perspective of the teachers. Jansen et al (2017) asked teachers to assess the bullying involvement of their students and explored the predictors of peer bullying perpetration and victimisation in a preschool classroom. On the other hand, Cameron and Kovac (2016) included the reports of parents as well as teachers and inquired about their views on the nature and extent of early childhood bullying.…”
Section: Quantitative Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repo and Sajaniemi (2015) examined teachers' institutional and pedagogical practices of prevention of preschool bullying, whereas Yörük (2016) investigated the nature and the extent of preschool bullying from the perspective of the teachers. Jansen et al (2017) asked teachers to assess the bullying involvement of their students and explored the predictors of peer bullying perpetration and victimisation in a preschool classroom. On the other hand, Cameron and Kovac (2016) included the reports of parents as well as teachers and inquired about their views on the nature and extent of early childhood bullying.…”
Section: Quantitative Assessmentsmentioning
confidence: 99%
“…Camodeca et al (2015) utilised the bullying involvement section of the Participant Roles Questionnaire (Belacchi & Farina, 2010), and provided internal reliability as well as the results of a confirmatory factor analysis. Using the items of Perren and Alsaker (2006), Jansen et al (2017) only reported internal reliability. Yörük's (2016) study was the only one in the last group with an independent instrument to examine peer bullying involvement of the preschool children.…”
Section: Reliability and Validity Problems In Quantitative Assessmentsmentioning
confidence: 99%